2016
DOI: 10.1136/emermed-2015-204968
|View full text |Cite
|
Sign up to set email alerts
|

‘Down-triage’ for children with abnormal vital signs: evaluation of a new triage practice at a paediatric emergency department in Japan

Abstract: Objective Assessment of abnormal vital signs in triage is a challenge in the paediatric emergency department (PED), since vital signs may reflect anxiety, fever or pain rather than the clinical deterioration of the child. We aimed to evaluate the efficacy of subjective 'down-triage' (change of the initially determined acuity levels) of Japanese Triage and Acuity Scale ( JTAS). Methods This is a retrospective cohort study of patients in PED up to 15 years of age at a tertiary paediatric medical centre in Japan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…Initial vital signs are recommended in assessing the level of PedKTAS ( 2 ); however, limitations have been noted when using the initial vital signs to determine the triage levels in children. Because children who are placed in unfamiliar environments become anxious and irritable, this effect may cause a shift of vital signs beyond the normal range ( 3 4 5 ). Therefore, although a child may have a non-emergent condition, the level of severity may seem to be higher when his or her initial vital signs are applied directly to determine the triage levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial vital signs are recommended in assessing the level of PedKTAS ( 2 ); however, limitations have been noted when using the initial vital signs to determine the triage levels in children. Because children who are placed in unfamiliar environments become anxious and irritable, this effect may cause a shift of vital signs beyond the normal range ( 3 4 5 ). Therefore, although a child may have a non-emergent condition, the level of severity may seem to be higher when his or her initial vital signs are applied directly to determine the triage levels.…”
Section: Introductionmentioning
confidence: 99%
“…This incorrect ‘over-triage’ can lead to overcrowding of the pediatric ED with an increased length of stay, unnecessary utilization of medical resources, increased medical costs, and potential threats to patients' safety ( 4 6 7 ). Therefore, a nationwide controversy has emerged regarding whether the vital signs of children should be directly applied to PedKTAS or whether a modified interpretation of vital signs should be used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we did not evaluate the inter‐observer reliability of the PAT among the staff in this study, but all the triage nurses in our hospital have been trained in Paediatric Advanced Life Support and this ensures that they consistently evaluate patients using the PAT. Studies of decisions made by our triage nurses have previously been shown to be useful for predicting patients’ needs in the emergency department . Second, we only performed this study at a single tertiary care institution in Japan and we diagnosed and treated the participants in accordance with the Japanese clinical guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…All the patients received in‐hospital triage by nurses specialised in paediatric emergency triage using the Japan Triage and Acuity Scale. All triage data were consecutively collected by an in‐hospital electronic triage system (eTriage, DankNet and DoWell Inc., Tokyo, Japan) and served as the mother cohort . The triage system was developed in accordance with previous literature .…”
Section: Methodsmentioning
confidence: 99%